2009
DOI: 10.4054/demres.2009.21.15
|View full text |Cite
|
Sign up to set email alerts
|

The Likoma Network Study: Context, data collection and initial results

Abstract: The extent and structure of sexual networks have important consequences for the spread of sexually transmitted diseases such as HIV. However, very few datasets currently exist that allow a detailed investigation of sexual networks in sub-Saharan African settings where HIV epidemics have become generalized. In this paper, we describe the context and methods of the Likoma Network Study (LNS), one of the few studies that have collected extensive information on sexual networks in sub-Saharan Africa. We start by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 57 publications
1
61
0
Order By: Relevance
“…With the exception of the Likoma Island Study,3 sexual networks are rarely observed directly, and most studies are restricted to the behaviour and serostatus of network ‘nodes’, that is, to the sexually active individuals in the community. This lack of information on network structure, and the transmission that occurs within these networks, fuels debate about the importance of certain aspects of the network including concurrency and transactional sex 4.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of the Likoma Island Study,3 sexual networks are rarely observed directly, and most studies are restricted to the behaviour and serostatus of network ‘nodes’, that is, to the sexually active individuals in the community. This lack of information on network structure, and the transmission that occurs within these networks, fuels debate about the importance of certain aspects of the network including concurrency and transactional sex 4.…”
Section: Introductionmentioning
confidence: 99%
“…We implemented this approach during the second round of the Likoma Network Study (LNS), a study of the networks of heterosexual relationships that connect the population of a small island of Lake Malawi [64, 65]. All inhabitants aged 18–49 years old were asked to (1) list their 5 most recent sexual partners using audio computer-assisted interviewing (ACASI, [64]), and (2) answer questions about their relationship with each of these partners.…”
Section: Methodsmentioning
confidence: 99%
“…All inhabitants aged 18–49 years old were asked to (1) list their 5 most recent sexual partners using audio computer-assisted interviewing (ACASI, [64]), and (2) answer questions about their relationship with each of these partners. All nominated partners were identified in rosters obtained through a household census, in order to reconstruct the population-level sexual networks of the island [64, 65]. In 520 sexual relationships, both partners were interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The interview guide to collect both egocentric and sociocentric data was developed using previously tested items and approaches used by the investigative team (Abbott, Stoller, & Rose, 2007;Hampton, 2011;Hampton & Wellman, 2003;Helleringer, Kohler, Chimbiri, Chatonda, & Mkandawire, 2009). Our goal was to develop an instrument and strategy that measured both egocentric and sociocentric social network information, from the residents' perspective, for use in larger longitudinal studies with both cognitively capable and cognitively impaired individuals.…”
Section: Data Collection Proceduresmentioning
confidence: 99%